2021
DOI: 10.1080/09540105.2020.1865281
|View full text |Cite|
|
Sign up to set email alerts
|

The relation between the sensitization to molecular components of inhalant allergens and food reactions in patients suffering from atopic dermatitis

Abstract: To evaluate the relation between the sensitization to molecular components of inhalant allergens and the occurrence of food reactions in atopic dermatitis patients. Another aim is to evaluate the semi-quantification results of the ISAC Multiplex testing to reveal the relevance of the leading allergens. The complete dermatological and allergological examination including the examination of the sensitization to molecular components with Multiplex ISAC testing was performed. The food reactions to examined food al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Study of IgE specificity revealed an association of sensitization to molecular components of pollen allergens with food reactions in patients suffering from atopic dermatitis. In patients suffering from reactions to peanuts, hazelnuts, celery, apple and peach, a significantly higher frequency of sensitization to major pollen allergens Bet v 1, Aln g 1, Phl p 1, 2, 4, 5, 6, 11 was found ( Čelakovská et al, 2021a ; Čelakovská et al, 2021b ). Interestingly, sensitization to Bet v 1 homologues and profilins is associated with mild symptoms (pollen eating syndrome), and sensitization to LTP homologues and seed storage proteins are associated with severe reactions ( Čelakovská et al, 2021a ).…”
Section: Sensitization To Pollen Allergensmentioning
confidence: 99%
“…Study of IgE specificity revealed an association of sensitization to molecular components of pollen allergens with food reactions in patients suffering from atopic dermatitis. In patients suffering from reactions to peanuts, hazelnuts, celery, apple and peach, a significantly higher frequency of sensitization to major pollen allergens Bet v 1, Aln g 1, Phl p 1, 2, 4, 5, 6, 11 was found ( Čelakovská et al, 2021a ; Čelakovská et al, 2021b ). Interestingly, sensitization to Bet v 1 homologues and profilins is associated with mild symptoms (pollen eating syndrome), and sensitization to LTP homologues and seed storage proteins are associated with severe reactions ( Čelakovská et al, 2021a ).…”
Section: Sensitization To Pollen Allergensmentioning
confidence: 99%
“…Side effects that may occur with this type of immunization are erythema, pruritus, eczema, and atopic dermatitis at the site of allergen application. EPIT has modest results in terms of inducing food tolerance (28-50%) [62][63][64]. As in the case of SLIT, the main limitation of the method is the amount of allergen that can be administered.…”
Section: Epicutaneous Immunotherapy (Epit)mentioning
confidence: 99%
“…It was shown that specific IgE-blocking IgG developed during sublingual immunotherapy (SLIT) with the recombinant Bet v 1 (rBet v 1-SLIT) were cross-reactive with Aln g 1; however, they were unable to fully prevent Aln g 1-induced effector cell activation in the case of the majority of patients [7]. In addition, it is worth noting that plant panallergens of other classes, in particular, profilins and polcalcins, may be involved in sensitization and be responsible for the low effectiveness of AIT in some patients [8].…”
Section: Introductionmentioning
confidence: 99%